The waqf institution funds management at public universities in Perlis, Malaysia - Ummi Aida Mat Nor; Hydzulkifli Hashim Omar; Noriza Abd Aziz; Solahuddin Abdul Hamid (Penerbit Universiti Kebangsaan Malaysia, 2021)
Waqf was recommended by Prophet Muhammad (PBUH) since the beginning of Islam up until this moment. Even though the term waqf is not explicitly mentioned in the Quran, it should be emphasized that the Quran provides clear guidance on the concept of wealth distribution to ensure the realization of social justice. Islam teaches that wealth is a trust from Allah and should be spent as He intends. Concerning the poor, Islam says the poor have their share in the wealth of the rich. Therefore, the role of waqf is more in the service of humanity where it brings enhancements to the socio-economic, harmony and prosperity of the Ummah. This research attempts to investigate the acceptance among students on the active roles of waqf institutions as well as to encourage Higher Education Institutions (HEIs) to develop their own sources of revenue with waqf funds. This study was conducted on 739 respondents comprising undergraduate students from public universities in Perlis in order to test the developed hypothesis to measure the factors that influence the acceptance of waqf institutions which include attitude, subjective norm, religiosity, amount of informationand awareness. The results reported in this research may propel the idea of the establishment of waqf institutions at selected public universities in Perlis and may eventually at all universities throughout the country. All the data were analysed using Statistical Package for Social Science (SPSS) version 23.0. A conceptual framework is built based on the Theory of Reasoned Action (TRA). The results suggested that only four factors, namely attitude, subjective norm, religiosity and awareness, are factors that influence the acceptance of the establishment of waqf institutions among undergraduate students at public universities in Perlis.